PSIV-B-25 Late-Breaking: Maternal supply of polyunsaturated fatty acids and methionine during late- gestation alters amino acid transporters and global DNA methylation in the lamb small intestine. (5th December 2019) - Relling, Alejandro E; Velazquez, Milca Rosa; Batistel, Fernanda
Abstract: The intestine plays a crucial role in nutrient digestion and absorption, and its function is critical for animal growth and health. However, the effect of maternal nutrition on offspring's intestine is not well documented. The objective of this study was to evaluate the effects of maternal supply of polyunsaturated fatty acids, methionine or both during late-gestation on offspring's intestine amino acids transporters and global DNA methylation. Twenty ewes were used in a randomized block design and treatments were arranged in a 2×2 factorial design. Treatments were: 1) control diet (CTR) without polyunsaturated fatty acids (PUFA) or methionine (MET) supplementation; or supplemented with 2) Ca salts of PUFA (1% DMI; Strata G113 ®, Virtus Nutrition); rumen-protected MET (0.1% DMI; Smartamine ®, Adisseo); and 4) PUFA and MET (PUFA+MET). Treatments were fed from day 100 to 145 of gestation. On day 145, ewes were euthanized and fetuses' intestines were sampled. Protein quantification of amino acid transporters was measured using Simple Western System and global DNA methylation was determined using a commercial kit. No interactions between PUFA×MET were observed for the variables analyzed. PUFA increased (P ≤ 0.03) global DNA methylation and protein expression of SLC7A5, SLC38A2, and SLC38A10 compared with CTR. Furthermore, PUFA tended to increase (P = 0.07) SLC38A1 protein expression compared with CTR, whereas no difference (P > 0.05) was observed for SLC6A9. Compared with CTR, MET increased (P ≤ 0.05) global DNA methylation and SLC38A10 protein expression, and tented to increase (P ≤ 0.10) SLC6A19 and SLC38A2. MET did not affect SLC7A5 and SLC38A1 compared with CTR. Maternal supply of PUFA and MET led to greater protein expression of amino acid transporters and global DNA methylation on offspring' intestine; however, the effects of these nutrients were not additive. Further research is necessary to better understand the role of DNA methylation on intestine's amino acid transporters.